Brachytherapy for stage IIIB squamous cell carcinoma of the uterine cervix: survival and toxicity - Zuliani,Antonio Carlos (2010)
OBJECTIVE: To compare survival and toxicity of three different treatments for stage IIIB cervix cancer: low-dose-rate (LDR), high-dose-rate (HDR) brachytherapy and association of HDR and chemotherapy. METHODS. Between 1985 and 2005, 230 patients with FIGO stage IIIB squamous cell carcinoma of the uterine cervix received 4-field pelvic teletherapy at doses between 40 and 50.4 Gy, with a different complementation in each group. The LDRB group, with 42 patients, received one or two insertions of LDR, with Cesium-137, in a total dose of 80 to 100Gy at point A. The HDR group, 155 patients received HDR in 4 weekly 7 Gy fractions and 9 Gy to 14.4 Gy applied to the involved parametria. The CHT group, 33 patients, were given the same treatment as the HDR group and received 5 or 6 weekly cycles of cisplatin, 40 mg per m2. RESULTS: The five-year progression-free survival (PFS) was 60% for the HDR group and 45% for the LDR group, and the two-year PFS for the CHT group was 65% (p = 0.02). The five-year Overall Survival (OS) was 65% for the HDR group and 49% for the LDR group. The two-year OS was 86% for the CHT group (p = 0.02). Rectum toxicity grade II was 7% for the LDR group, 4% for the HDR group and 7% for the CHT group that had one case of rectum toxicity grade IV. CONCLUSION: Patients that received HDR had better OS and PFS. The Chemotherapy-HDR association showed no benefit when compared to HDR only. Toxicity rates showed no difference between the three groups.